Perkembangan Populasi dan Serangan Thrips parvispinus Karny (Thysanoptera: Thripidae) pada Fenologi Tanaman Cabai Besar di Tiga Ketinggian Tempat di Bali - I NGURAH MEGA MERTA; NI NENGAH DARMIATI; I WAYAN SUPARTHA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Population Development and Plant Damase by Thrips parvispinus Karny (Hemiptera: Aphididae) On the Phenology of Chili in the Three Elevation Level in Bali The aim of this research was to know the development of population, T. parvispinus plant damase and the production of chilly at three different elevation ie, Sedang Village 150 meters above sea level, Kerta Village 650 meters above sea level, and Songan Village 1000 meters above sea level. This research was using sistimatihic method wits U shape, and replicated 5 times. The each of replicatin was taken to sample points. This research was done starting from Desember 2016 to Februari 2017. The results of the three research sites showed that in all three sites the population development and damase percentage by T. parvispinus was highest on observation at 7 (Week After Transplant). The highest population abundance in Kerta Village 7.67 / one flower was followed by Sedang Village 5.76 / one flower and by Songan Village 4.08 / one flower. The highest percentage damage in Kerta Village 55.95% followed by Sedang Village 41.34% and Songan Village 16.67%. This indicated that population development affects the percentage of damage. From the three research sites there was a difference of production which were the weight of harvest in Songan Village 709 g, in Kerta Village 514 g and in Sedang Village 698 g /10 plant.